Embodied knowledge, mediated practice: A critical examination of digital integration in Qur'anic tahsin pedagogy - Syafi'i, Imam (Institute of Information Technology and Social Science (IITSS), 2026)
Digitalization has rapidly expanded access to Qur'anic tahsin learning, yet existing scholarship often prioritizes technological adoption while giving limited attention to how religious authority, social interaction, and sacred meaning are negotiated in online environments. This study examines online tahsin at Universitas Terbuka, Indonesia, as a socio-pedagogical space where tradition, pedagogical authority, and digital mediation intersect within contemporary distance education. Using an explanatory sequential mixed-method design, the research began with a survey of 56 students from several Indonesian provinces in 2025, employing a five-point Likert scale to explore learning experiences, digital readiness, technical challenges, and perceptions of tutor feedback. This quantitative phase was followed by semi-structured interviews to deepen interpretation of the statistical findings. The results show that tutor authority is reconstructed in virtual settings through sustained corrective interaction, precise recitation guidance, and pedagogical practices that emphasize adab and ethical responsibility. These processes enhance recitation accuracy, affective engagement, and learner confidence, including dimensions of spiritual experience, despite structural constraints that continue to shape the quality of interaction.